Sustainability assessments of bio-based polymers - Hottle, Troy A.; Bilec, Melissa M.; Landis, Amy E. (Polymer degradation and stability, 2013)
Bio-based polymers have become feasible alternatives to traditional petroleum-based plastics. However, the factors that influence the sustainability of bio-based polymers are often unclear. This paper reviews published life cycle assessments (LCAs) and commonly used LCA databases that quantify the environmental sustainability of bio-based polymers and summarizes the range of findings reported within the literature. LCA is discussed as a means for quantifying environmental impacts for a product from its cradle, or raw materials extraction, to the grave, or end of life. The results of LCAs from existing databases as well as peer-reviewed literature allow for the comparison of environmental impacts. This review compares standard database results for three bio-based polymers, polylactic acid (PLA), polyhydroxyalkanoate (PHA), and thermoplastic starch (TPS) with five common petroleum derived polymers. The literature showed that biopolymers, coming out of a relatively new industry, exhibit similar impacts compared to petroleum-based plastics. The studies reviewed herein focused mainly on global warming potential (GWP) and fossil resource depletion while largely ignoring other environmental impacts, some of which result in environmental tradeoffs. The studies reviewed also varied greatly in the scope of their assessment. Studies that included the end of life (EOL) reported much higher GWP results than those that limited the scope to resin or granule production. Including EOL in the LCA provides more comprehensive results for biopolymers, but simultaneously introduces greater amounts of uncertainty and variability. Little life-cycle data is available on the impacts of different manners of disposal, thus it will be critical for future sustainability assessments of biopolymers to include accurate end of life impacts.